Applications of CRISPR/Cas9 as New Strategies for Short Breeding to Drought Gene in Rice - Park, Jae-Ryoung; Kim, Eun-Gyeong; Jang, Yoon-Hee; Jan, Rahmatullah; Farooq, Muhammad; Ubaidillah, Mohammad; Kim, Kyung-Min (Frontiers in Plant Science, 2022)
Recent unpredictable climate change is the main reason for the decline in rice yield. In particular, drought stress is a major constraint in reducing yield and quality for rice at rainfed agriculture areas such as Asia and South America. CRISPR/Cas9 provides an effective solution for gene function study and molecular breeding due to specific editing of targeted genome sequences. In addition, CRISPR/Cas9 application can significantly reduce the time required to develop new cultivars with improved traits compared to conventional complex and time-consuming breeding. Here, drought-induced gene Oryza sativa Senescence-associated protein (OsSAP) was edited by CRISPR/Cas9. To investigate the possible role of OsSAP in drought stress, genome-editing plants were subjected to drought stress until the soil moisture content reached 20%, and the reactive oxygen species (ROS) scavenging efficiency of genome-editing plants were decreased. When the genome-editing plants were subjected to drought stress, survival rate, shoot length, root length, content of chlorophyll number of tiller, and 1,000-grain weight decreased, and more H2O2 and O2− were detected in leaves. In addition, expression levels of several critical stress-related transcription factors were decreased in the OsSAP genome-editing plant. These results suggest that OsSAP function as a positive regulator during drought stress response in rice. We analyzed the expression of OsSAP and Cas9 in G0 and G1 plants as well as G2 seeds. As the course of generation advancement progressed, Cas9 expression remained stable or weakened but the OsSAP expression was continuously removed from the G0 plant. The coefficient of variation in both G1 plants and G2 seeds were lower than 5%. Overall, our results suggest that CRISPR/Cas9 could be a novel and important tool for efficiently generating specific and inheritable targeted genome editing in rice, with short breeding cycles.